Fast and Efficient Synthesis of 4-Arylidene-3-phenylisoxazol-5-ones - Maryam Mirzazadeh; Gholam Hossein Mahdavinia (E-Journal of Chemistry)
A convenient and easy synthesis of 4-arylidene-3-phenylisoxazol-5-ones by the three-component reaction of hydroxylamine, ethyl benzoylacetate and aromatic aldehydes in the presence of DABCO in refluxing ethanol is reported.